Sister Chromatid Differentiation and Chromosomal Insitu Suppression Hybridization - A Combined Methodology for Analyzing Cell-Proliferation and Sces in Individual Chromosomes - Knuutila, Sakari (1992)
Fil: Knuutila, Sakari. Department of Medical Genetics. University of Helsinki; Finland